Analysis of the Impact of High Acuity Rehabilitation Beds in Reducing Readmission Rate to Acute Care - Sammartino, Francesco; Yu, Eunkyung; Huffman, Tracy; Harris, Angela; Musto, Maureen; Schultz, Sarah; Callicoat, McKenzie; Bavishi, Sheital (American journal of physical medicine & rehabilitation, 2025)
The aim of this study is to describe the use of the high acuity rehabilitation program at an academic rehabilitation institution to limit the readmission rate to acute care hospitals. Retrospective data from inpatient admissions and discharges between January 2019 and June 2023 were used for this study. Modeling was performed using stepwise regression to select intrinsic and extrinsic patient factors associated with acute admission status. The model performance was assessed using confusion matrices and receiver operating characteristic curves. Among the 199 patients who utilized the high acuity rehabilitation program unit from January 2019 to June 2023, 96 were discharged acutely to a hospital, while 103 were discharged to home, skilled nursing facility, or long-term acute care facility. The most frequent impairment groups among high acuity rehabilitation program users were brain injury (22%), debility (21%), and spinal cord injury (18%). The improvement in GG scores for self-care and mobility was associated with successful discharges to nonacute care settings. Unplanned discharges from rehabilitation to acute care are a reason for prolonged hospital stays and increased financial burden on patients. The implementation of a high acuity rehabilitation program can help in the management of temporary medical conditions.